Relationship Between Adversity Quotient (AQ) and Mathematics Learning Motivation Among Generation Z in Digital Era - Siirsani Siirsani; Rika Sukmawati; Nisvu Nanda Saputra (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2026)
This study aims to analyze the effect of Adversity Quotient (AQ) on mathematics learning motivation among Generation Z in the digital era. The background of this research is based on low student motivation influenced by technological distractions and lack of resilience in learning difficulties. This study used a quantitative approach with simple linear regression analysis. Data were collected through questionnaires distributed to students. The results show that AQ has a positive and significant effect on learning motivation, with a regression coefficient of 0.135 and significance value of 0.003 (<0.05). The R Square value of 0.138 indicates that AQ contributes 13.8% to learning motivation. Therefore, it can be concluded that higher AQ leads to higher mathematics learning motivation.